PARTISIPASI DAN HASIL BELAJAR KOGNITIF SISWA PADA PEMBELAJARAN BIOLOGI DENGAN PENDEKATAN FLIPPED CLASSROOM - Faisal, Faisal; Jumadi, Oslan (FKIP, Universitas Muslim Maros, 2024)
This study aims to determine the implementation of the flipped classroom learning model on cognitive learning outcomes and student participation during the learning process of grade XI SMA Negeri 1 Bantaeng on human coordination system material. This type of research is Pre-Experimental Design with One-Shot Case Study research design. The data collection technique used is in the form of an essay test of 10 questions and observation sheets of student participation. The results of the statistical test showed the average post-test score in class XI Science 5 which was 86.13. The Minimum Completeness Criteria (KKM) obtained by students with a percentage of 96.7% are on the completion criteria, and 3.3% are on the incomplete criteria. The average student participation during the learning process in online classes (google classroom) is 83% with the very active category, and student participation during the learning process in class is 65% with the active category. The conclusion of this study is that the implementation of the flipped classroom learning model can improve cognitive learning outcomes and learning participation of grade XI students of SMA Negeri 1 Bantaeng on human coordination system material.